Fundamentals of Business Process Management - Dumas, Marlon; Rosa, Marcello La; Mendling, Jan; Reijers, Hajo A. (Springer, 2018)
Almost 5 years ago, we decided to join forces and deliver a textbook on Business Process Management (BPM). Since then, BPM has grown more important than ever. Businesses around the world are carrying out BPM initiatives with the aim to outperform their competitors or meet the demands of regulatory authorities. At the same time, a lively academic community is pushing the boundaries of the discipline: computer scientists, management scientists, and engineers add new elements to its repertoire, which are eagerly being picked up by practitioners. We felt that having a textbook available that organizes the broad spectrum of the topic would help us teaching at our institutions about the fascinating concepts, methods, and technologies behind BPM. What is more, we hoped that a textbook on BPM would also enable a broader audience beyond the students in our own classrooms to learn about its marvels. When the first edition of the book hit the shelves in early 2013, it became clear to us that our textbook met an unsaturated demand. The book quickly became the basis for BPM courses at around 200 universities across the continents. Lecturers around the world reached out to us to discuss the material and a community of BPM educators evolved from these interactions. We traveled to various institutions ourselves to deliver guest lectures on the basis of the book and, from time to time, also stepped into the corporate world to preach the BPM gospel. The demand was such that we were compelled to produce a Massive Open Online Course (MOOC) based on the textbook, which brought together over 7,500 participants in its first delivery and over 25,000 in total after several deliveries. In a sense, our mission seemed to be accomplished. But then again, we knew it was not.